IMPLEMENTATION MENTAL NURSING CARE IN PATIENTS WITH HALLUCINATIONS AND HEFEBRENIC SCHIZOPHRENIA - Nova, Renny; Zevriana, Meylida Richa; Sunarto, Muhammad (Universitas Airlangga, 2025)
Background Schizophrenia is a chronic mental disorder characterized by disorganized thoughts, speech, and behavior. In the hebephrenic subtype, patients often exhibit childish, purposeless behavior and experience mild hallucinations or delusions. One of the core symptoms—hallucinations—reflects an impaired ability to distinguish internal from external stimuli, potentially resulting in loss of self-control and harmful actions. This study aimed to describe the mental nursing care provided to Mr. D, a patient with hallucinations and hebephrenic schizophrenia. Method This case study used an analytical approach to psychiatric nursing care with a descriptive design. Data were obtained through subjective and objective assessment, followed by problem identification, nursing diagnoses, intervention planning, implementation, and evaluation, all presented descriptively. Result After six days of nursing care, the patient showed significant improvement in managing hallucinations, communicating effectively, following structured activities, and adhering to medication. There was also a noticeable decrease in the frequency and intensity of hallucination-related symptoms. Conclusion Targeted nursing interventions improved the patient’s ability to manage hallucinations, engage socially, and maintain treatment compliance. These results underscore the importance of